ASPECTS OF THE CURRENT FOCUS OF TENSION IN THE EUROPEAN UNION - Å evÄÃkovÃ¡, Michaela (European Scientific Journal, ESJ, 2016)
The main purpose of this paper is to explore the current status of the European Union and Eurozone, focusing on economic and political aspects and in the context of decisions made quite recently. The contemporary crises have shown that especially the common monetary policy of the ECB and single interest rate are inadequate for all euro area members and caused deterioration in the economic situation of some peripheral countries. The paper elaborates on the main flaws of the EU and Eurozone, highlights and draws attention to a vacuum of European law in the case of the option to leave the Eurozone. The paper critically analyses decision-making carried out at European level by the political class where the reality of European specifics and the continentâ€™s historic development was ignored.